Nature and magnitude of aromatic base stacking in DNA and RNA: Quantum chemistry, molecular mechanics, and experiment - Sponer, Jiří; Sponer, Judit E; Mládek, Arnošt; Jurečka, Petr; Banáš, Pavel; Otyepka, Michal (Biopolymers, 2013)
Base stacking is a major interaction shaping up and stabilizing nucleic acids. During the last decades, base stacking has been extensively studied by experimental and theoretical methods. Advanced quantum-chemical calculations clarified that base stacking is a common interaction, which in the first approximation can be described as combination of the three most basic contributions to molecular interactions, namely, electrostatic interaction, London dispersion attraction and short-range repulsion. There is not any specific π-π energy term associated with the delocalized π electrons of the aromatic rings that cannot be described by the mentioned contributions. The base stacking can be rather reasonably approximated by simple molecular simulation methods based on well-calibrated common force fields although the force fields do not include nonadditivity of stacking, anisotropy of dispersion interactions, and some other effects. However, description of stacking association in condensed phase and understanding of the stacking role in biomolecules remain a difficult problem, as the net base stacking forces always act in a complex and context-specific environment. Moreover, the stacking forces are balanced with many other energy contributions. Differences in definition of stacking in experimental and theoretical studies are explained.
Keywords: simulace molekulární dynamiky; termodynamika; quantum-chemical calculations; Thermodynamics; Models, Molecular; stacking; molekulární modely; Molecular Dynamics Simulation; Quantum Theory; nucleic acids; DNA; RNA; kvantová teorie